La planificación estratégica como aprendizaje. - LIP LICHAM, Cesar (2012)
No person or organization knows enough like to solve everything in advance. Although big lines can betraced to guide institutional work, the unpredictable become forces them to develop active learning actioncourses. Of these courses, the strategic planning is the one that had produced the optimum and the mostlingering successful results. The strategic learning implies that the person or organization has to mobilizein a continuous line which extreme limits are, on one hand, the totally premeditated strategies, and on theother hand, the fully emergent strategies. To learn strategically it is required to release the mind in orderto slip flexibly in the continuous line and to accomplish that the possible action courses will be created froma fertile dialogue between the thought and the action. In this article we describe the main prior andcurrent ideas of the strategic planning, that considered as a learning process, has a paradoxical nature,where the final product is the process.